Hoffmann Reflex Measured From Lateral Gastrocnemius Is More Reliable Than From Soleus Among Elderly With Peripheral Neuropathy - Song, Qipeng; Sun, Mengzi; Lewis, Kelsey; Choi, Jung Hun; Manor, Brad; Li, Li (Frontiers in Aging Neuroscience, 2022)
Introduction: Peripheral neuropathy (PN) affects up to 20% of the population over the age of 60, damages peripheral nerves, and leads to central nervous system (CNS) modulation. Hoffmann reflex (H-reflex) may better assess PN adaptation than the commonly used nerve conduction velocity test because it assesses the function of the peripheral neural system and CNS modulation. One of the previous studies indicated that the H-reflex in soleus (SO) had poor reliability among the PN population. This project aimed to find a reliable muscle among triceps surae muscles during standing and walking among the PN population. Materials and Methods: Sixteen older adults (>65 years of age) diagnosed with PN were recruited in this study. The H-reflex test was conducted on the muscle belly of the SO, MG, and LG during standing and walking (heel contact, midstance, and toe-off phases). All measurements were collected on two occasions, separated by at least seven days. Intraclass correlation coefficients (ICCs) and their confidence intervals (CIs) were used to examine the consistency of the H-reflex outcome variables, H-index and H/M ratio, between the repeated tests for all three tested muscles. Results: The ICCs of H-index during standing and the three walking phases were poor to moderate in SO (0.486 0.737) and MG (0.221 0.768), and moderate to high in LG (0.713 0.871). The ICCs of H/M ratio were poor to moderate in SO (0.263 0.702) and MG (0.220 0.733), and high in LG (0.856 0.958). Conclusion: The H-reflex of LG was more reliable than SO and MG during standing and walking among older adults with peripheral neuropathy. It is crucial for future studies in this population to study H-reflex of LG, not SO and MG, for more reliable results.